Simulasi unjuk kerja kolektor surya hybrid PV/T berdasarkan jarak susunan pipa absorber berbentuk spiral - Ahmad Yonanda; Amrizal Amrizal; Harmen Harmen; Hadi Prayitno (TURBO [Tulisan Riset Berbasis Online], 2022)
The performance of the solar collector can be reviewed based on several parameters, namely thermal and large fluid drop (pressure drop). This study aims to compare the thermal and pressure drop performance of plate-type solar collectors based on a spiral-shaped pipe arrangement using the distance between the pipes. The comparison of performance analyzed in each study for the distance between the pipes is 25 mm and 50 mm. The approach or stage of research on the performance of the data plate type solar collector is through CFD simulation testing. The simulation stages that will be carried out include: making the geometric design of the solar collector and selecting the mesh method used by the polyhedral type. The results of the solar collector test carried out by CFD simulation show that the use of a 50 mm absorber pipe arrangement has a higher thermal efficiency when compared to the 75 mm absorber pipe arrangement and also a 49.45% increase in pressure drop.